Direct Torque Control of Two Induction Motors Using the Nine-Switch Inverter - Draoui Abdelghani; Allaoua Boumediène (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The Nine-Switch Inverter(NSI) is a recently developed dual output converter. It can be used to drive two three-phase loads independently. As a substitute to two separate conventional voltage source inverters, the NSI has been, already, proposed in various industrial applications to reduce the numberof semiconductor switches and its associated energy losses and drive circuitry. On the other hand, the Direct Torque Control(DTC) is a robust control scheme of AC motors, which consist of selecting proper state vectors of a conventional voltage source inverter. The NSI, having a different working principle from the conventional voltage source inverter and taking into account the varying influence of active space vectors on motor’s torque and stator flux, a Direct Torque Control is suggested in this paper to, efficiently, drive two induction motors independently, while minimizing the torque and stator flux ripples of both motors. Simulations results confirm the effectiveness of the proposed algorithm. In addition, application of this newly proposed control scheme in operation of an Electric Vehicule(EV) is demonstrated.